(untitled) (Colloquia Comparativa Litterarum, 2025)
For over a century now, dystopian visions of the future have been an integral part of the strategies through which literature reacts to changes in the world. However, dystopia is not always an entirely new world. Sometimes, it is an element in a world born from a utopian impulse. The article explores the variations of the dystopian in two such worlds influenced by the works of William James: Bernard Wolfe’s Limbo and in Ursula K. Le Guin’s The Ones Who Walk Away From Omelas. The analysis adopts the concept of dystopia as utopia’s shadow, and traces the moments when the world, the body, and the language of the Utopian begin to waver and transform into the voice of the Dystopian.